Inhibitory effect of procyanidin B2 and tannin acid on cholesterol esterase and their synergistic effect with orlistat - Xiangxin Li; Yijing Pu; Haitao Jiang; Wenxiao Jiao; Wenjun Peng; Wenli Tian; Weibo Jiang; Xiaoming Fang (Food Science and Human Wellness)
This study was aimed to analyze the effect of procyanidin B2 (PC) and tannin acid (TA) on the activities of cholesterol esterase (CEase) and the inhibitory mechanisms of enzymatic activity. The interaction mechanisms were investigated by enzymatic kinetics, multi-spectroscopy methods, thermodynamics analysis, molecular docking, and dynamic simulations. PC and TA could bind with CEase and inhibit the activity of enzyme in a mixed-competitive manner and non-competitive manner, which was verified by molecular docking simulations and dynamics simulations. Also, PC and TA showed the synergistic inhibition with orlistat. Fluorescence, UV-vis and the thermodynamic analysis revealed that the complexes were formed from CEase and inhibitors by noncovalent interaction. As revealed by the circular dichroism results, both PC and TA decreased enzymatic activities by altering the conformations of CEase. The inhibition of PC and TA on CEase might be one mechanism for its cholesterol-lowering effect.